NILAI-NILAI KEARIFAN LOKAL TRADISI KATOBA DALAM BUDAYA MASYARAKAT MUNA DI KOTA KENDARI - Ashmarita Ashmarita; Hasniah Hasniah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
This study aims at describing the values of local wisdom in society and can be a way out to overcome the moral problems. This research is important because today there is a phenomenon of attitudes and behaviors that are less virtuous among pupils, youth, and young generation, while character education in schools has not gone well. The research method used is descriptive qualitative, by selecting informant by purposive sampling. The results showed that: first, Muna society in Kendari city has a model of character education based on local wisdom, katoba tradition of the society. Second, the katoba-based character education model aims at introducing religious values early on children in 7-12 years old, inculcating basic moral teachings in children by introducing things that contain goodness and badness in muna mimotehi be nimokodo (things banned and allowed), teaching children values to respect social life, and avoiding things that do not belong to them (hakunasi).